An investigation of the nature and effects of the learning environment in agricultural science classrooms in Nigeria - Idiris, Suleiman Alhaji (Curtin University, 1994)
This study consolidates a long tradition of research involving the development/adaptation and validation of instruments assessing students' perceptions of psychosocial aspects of their classroom learning environments, and their use in investigating both the effects of classroom environment on student outcomes and determinants of classroom environment. The present study is distinctive, however, in that it is one of the few such studies conducted in Nigeria and the first classroom environment study conduced specificallly in agricultural science classrooms.The sample consisted of 1 175 students in 50 classes in 20 schools in eight states and the Federal Capital Territory. Both the individual student and the class mean were used as units of statistical analysis. The classroom environment instrument assessed negotiation, autonomy, student centredness, investigation and differentiation, and the student outcomes were attitudes, enquiry skills and practical performance.Each classroom environment scale was found to have satisfactory internal consistency reliability and discriminant validity and to differentiate between the perceptions of students in different classrooms. Satistically significant associations were found between classroom environment and the two student outcomes of attitudes and enquiry skills, but not for practical performance. When classroom environment dimensions were used as dependant variables, significant differences were found between schools with different school-level environments and between schools in forest and savanna regions.